Diagnostic value of exhaled nitric oxide to detect interstitial lung disease in systemic sclerosis - Tiev, K.p.; Coste, J.; Ziani, et al., M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background and aim: Increased alveolar concentration of nitric oxide (CANO) is related to the severity of interstitial lung disease (ILD) in systemic sclerosis (SSc). However, cut-off levels of CANO to rule out, or to rule in, the presence of ILD in individual patients are unknown.We aimed to assess the validity of CANO for the diagnosis of ILD in SSc and to determine the thresholds of CANO that can be used in clinical practice to predict the likelihood of ILD in SSc. Methods: Lung HRCT scan, PFTs and partitioned exhaled NO measurements were performed in 65 consecutive SSc patients. ILD was diagnosed on pulmonary HRCT according to the presence of ground glass or reticular opacities. Diagnostic performance of CANO for ILD diagnosis was assessed using ROC curves. Results: 38 out of 65 SSc patients had ILD. CANO, at a cut-off level of 4.3 ppb, had a sensitivity and specificity for the diagnosis of ILD of 87% (95% CI: 77 to 99) and 59% (95% CI: 41 to 78), respectively. The same cut-off level of CANO could detect impairment of gas exchange with a sensitivity and specificity of 78% (95% CI: 67 to 90) and 73% (95% CI: 46 to 99), respectively. Moreover, ILD could be ruled in (positive predictive value > 95%) when CANO 3 10.8 ppb, and ruled out CANO values 2 3.8 ppb (negative predictive value > 95%). Conclusion: CANO could be a valid non-invasive biological marker of ILD in SSc, and be of use in clinical practice.